A comparative study of the oral condition and the oral hygiene practices of children of dentists and of non-dentists - Balajadia, Ma. Concepcion L.
Sixty-seven children of dentists and an equal number of children of non-dentists were interviewed about their oral hygiene practices using questionnaired and then were given oral examination of determine their oral health status. These data were then compared to see if the oral hygiene practices and oral health status of the two groups differed significantly from each other. The difference in the latter was slight and was reflective of certain oral hygiene practices where significant differences between the two groups existed. These practices are concerned with the use of dental floss, frequency of scaling and polishing and dental visits, and the dentists visited (whether family, school or any dentist.